Location-Based Services and Privacy Protection under Mobile Cloud Computing - Yan, Yan; Xiaohong, Hao; Wanjun, Wang (Institute of Advanced Engineering and Science, 2015)
Location-based services can provide personalized services based on location information of moving objects and have already been widely used in public safety services, transportation, entertainment and many other areas. With the rapid development of mobile communication technology and popularization of intelligent terminals, there will be great commercial prospects to provide location-based services under mobile cloud computing environment. However, the high adhesion degree of mobile terminals to users not only brings facility but also results in the risk of privacy leak. The paper introduced the necessities and advantages to provide location-based services under mobile cloud computing environment, stressed the importance to protect location privacy in LBS services, pointed out new security risks brought by mobile cloud computing, and proposed a new framework and implementation method of LBS service. The cloud-based LBS system proposed in this paper is able to achieve privacy protection from the confidentiality of outsourced data and integrity of service results, and can be used as a reference while developing LBS system under mobile cloud computing environment.